Inhibitory effects of lapachol on rat C6 glioma in vitro and in vivo by targeting DNA topoisomerase I and topoisomerase II. Issue 1 (December 2016) - Xu, Huanli; Chen, Qunying; Wang, Hong; Xu, Pingxiang; Yuan, Ru; Li, Xiaorong; Bai, Lu; Xue, Ming
Abstract Background Lapachol is a natural naphthoquinone compound that possesses extensive biological activities. The aim of this study is to investigate the inhibitory effects of lapachol on rat C6 glioma both in vitro and in vivo, as well as the potential mechanisms. Methods The antitumor effect of lapachol was firstly evaluated in the C6 glioma model in Wistar rats. The effects of lapachol on C6 cell proliferation, apoptosis and DNA damage were detected by 3-(4, 5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium (MTS)/ phenazinemethosulfate (PMS) assay, hoechst 33358 staining, annexin V-FITC/PI staining, and comet assay. Effects of lapachol on topoisomerase I (TOP I) and topoisomerase II (TOP II) activities were detected by TOP I and TOP II mediated supercoiled pBR322 DNA relaxation assays and molecular docking. TOP I and TOP II expression levels in C6 cells were also determined. Results High dose lapachol showed significant inhibitory effect on the C6 glioma in Wistar rats (P  < 0.05). It was showed that lapachol could inhibit proliferation, induce apoptosis and DNA damage of C6 cells in dose dependent manners. Lapachol could inhibit the activities of both TOP I and II. Lapachol-TOP I showed relatively stronger interaction than that of lapachol-TOP II in molecular docking study. Also, lapachol could inhibit TOP II expression levels, but not TOP I expression levels. Conclusion These results showed that lapachol could significantly inhibit C6 glioma both in vivo and in vitro, which might be related with inhibiting TOP I and TOP II activities, as well as TOP II expression.